Protein metabolism in preterm infants with particular reference to intrauterine growth restriction. Issue 4 (21st June 2007) - de Boo, H A; Harding, J E
Abstract : There is growing evidence that neonatal and long-term morbidity in preterm infants, particularly those born before 32 weeks' gestation, can be modified by attained growth rate in the neonatal period. Guidelines for optimal growth and the nutritional intakes, particular of protein, required to achieve this are not well defined. Due to delays in postnatal feeding and a lack of energy stores developed in the last trimester of pregnancy, preterm infants often suffer early postnatal catabolism until feeding is established. There are indications that infants born with intrauterine growth restriction have perturbations in protein metabolism. Therefore, they may have different protein requirements than appropriate for gestational age infants. This review summarises what is known about protein requirements and metabolism in the fetus and preterm infant, with particular emphasis on the distinct requirements of the growth-restricted infant.